Engaging with the Nagoya Protocol on Access and Benefit-Sharing: recommendations for noncommercial biodiversity researchers - Collela, Jocelyn P. (2023)
The Convention on Biological Diversity and the Nagoya Protocol on Access and Benefit-Sharing provide an international legal framework that aims to prevent misappropriation of the genetic resources of a country and ensure the fair and equitable sharing of benefits arising from their use. The legislation was negotiated at the behest of lower-income, biodiverse countries to ensure that benefits derived from research and development of genetic resources from within their jurisdictions were equitably returned and could thereby incentivize conservation and sustainable use of biodiversity. Despite good intentions, however, rapid adoption of access and benefit-sharing measures at the national level, often without participatory strategic planning, has hampered noncommercial, international collaborative genetic research with counterproductive consequences for biodiversity conservation and sustainable use. We outline how current implementation of the Convention of Biological Diversity and the Nagoya Protocol affect noncommercial research, such as that conducted in many disciplines in biology, including mammalogy. We use a case study from Brazil, an early adopter, to illustrate some current challenges and highlight downstream consequences for emerging pathogen research and public health. Most emerging pathogens colonize or jump to humans from nonhuman mammals, but noncommercial research in zoonotic diseases is complicated by potential commercial applications. Last, we identify proactive ways for the mammalogical community to engage with the Convention on Biological Diversity and the Nagoya Protocol, through sharing of nonmonetary benefits and working with local natural history collections. Leveraging international scientific societies to collectively communicate the needs of biodiversity science to policy makers will be critical to ensuring that appropriate accommodations are negotiated for noncommercial research.